Bentuk, Makna, Fungsi Ritual Natoik Masyarakat Rote Desa Dalek Esa Kecamatan Rote Barat Daya Kabupaten Rote Ndao: Indonesia - Yublina Narang; Ronni M. Ndun; Sanhedri Boimau (Universitas Persatuan Guru 1945 NTT, 2026)
This research aims to find out the Form, Meaning and Function of the Natoik Ritual of the Rote Community in Dalek Esa Village and to find out the Description of the Form, Meaning and Function of the Natoik Ritual of the Rote Community in Dalek Esa Village, District, Southwest Rote, Rote Ndao Regency. The benefits of this research can add insight and knowledge, research on the Form, Meaning and Function of the Rote Community Natoik Ritual in Dalek Esa Village, District, Southwest Rote, Rote Ndao Regency. This research uses a qualitative descriptive method. The theory used is cultural linguistic theory. The results show that the implementation of the Natoik ritual is divided into three parts, namely, (1) initial ritual preparation; (2) ritual implementation; and (3) closing. While the meaning contained in the Natoik ritual is as follows: (1) Farewell meaning; (2) Consolation meaning; (3) Religious meaning, and (4) Spiritual meaning. The function of the Natoik ritual consists of 3 parts, namely (1) Poetic function; and (3) Directive function.